23-Valent Pneumococcal Polysaccharide Vaccine Uptake in the United States Air Force HIV Program. (July 2016) - Ocampo, Thad F.; Le, Tuan; Matthews, Peter E.; Okulicz, Jason F.
Streptococcus pneumoniae infection is a predominant cause of bacterial infection in HIV-infected individuals. However, reported rates of pneumococcal vaccination with 23-valent polysaccharide vaccine (PPV23) are variable. We evaluated uptake of PPV23 in patients diagnosed with HIV between 1996 and 2012 (n = 507) in the United States Air Force, a centralized HIV program with free access to care including vaccines and medications. A total of 411 (81.1%) patients received at least 1 PPV23 dose. The PPV23 vaccination within 1 year of diagnosis was greater for those diagnosed between 2004 and 2012 (n = 184, 86%) compared with 1996 to 2003 (n = 104, 56.5%; P < .001). For those with ≥6 years of follow-up, receipt of a second recommended PPV23 dose was greater for those diagnosed between 1996 and 2003 (n = 52, 57.8%) compared with 2004 to 2012 (n = 9, 28.1%; P = .004). Although first PPV23 vaccination was high in recent years, process improvement efforts are underway to overcome barriers and improve uptake of pneumococcal vaccines in our program.